Electromagnetic modeling and design of a novel class of complementary split‐ring resonators. Issue 4 (19th November 2018) - Rubio Martínez‐Dueñas, Enrique J.; Moreno de Jong van Coevorden, Carlos; Stukach, Oleg V.; Panokin, Nikolay V.; Gielis, Johan; Caratelli, Diego
Abstract: This research study reports the assessment of complementary split ring resonators based on Gielis transformation as basic elements for the design of high‐performance microwave components in printed technology. From the electromagnetic simulation of said structures, suitable equivalent circuit models are extracted and analyzed. Physical prototypes are fabricated and tested for design validation. The obtained results confirm that the adoption of supershaped geometries enables the synthesis of very compact scalable microwave filters.